OP0036 METHOTREXATE AND RHEUMATOID ARTHRITIS ASSOCIATED INTERSTITIAL LUNG DISEASE. (2nd June 2020) - Juge, P. A.; Lee, J. S.; Lau, J.; Kawano, L.; Rojas-Serrano, J.; Sebastiani, M.; Koduri, G.; Matteson, E.; Bonfiglioli, K.; Sawamura, M.; Kairalla, R.; Cavagna, L.; et al.
Abstract : Background: Methotrexate (MTX) is a key anchor drug for rheumatoid arthritis (RA) management. Its use has been associated with hypersensitivity pneumonitis and diffuse lung disease. Whether MTX exposure increases the risk of interstitial lung disease (ILD) in patients with RA is disputed. Objectives: We aimed to evaluate the association of antecedent MTX use with development of RA-ILD. Methods: Through a case-control study design with derivation and international validation samples, we examined the association of MTX exposure with ILD in 482 patients with RA-ILD and 741 patients with RA without ILD. Estimates were pooled over the different samples using meta-analysis techniques. Results: Analysis of the derivation sample revealed an inverse relationship between MTX exposure and RA-ILD (adjusted odds ratio [OR], 0.48; 95% confidence interval [CI], 0.25 to 0.92; P=0.028), which was confirmed in the validation samples (pooled adjusted OR, 0.39; 95% CI, 0.23 to 0.68; P<0.001). The combined estimate using both the derivation and validation samples revealed an adjusted OR of 0.43 (95% CI, 0.28 to 0.65; P<0.0001). MTX ever users were less frequent among patients with RA-ILD compared to those without ILD, irrespective of chest high resolution computed tomography pattern. In patients with RA-ILD, ILD onset was significantly delayed in MTX ever users compared to never users (11.5 ± 10.6 years and 3.7 ± 7.1 years, respectively; P<0.001). Conclusion: Our results suggest that MTX is not a risk factor for RA-ILD and support a possible disease modifying effect of MTX on development of RA-ILD. Disclosure of Interests: Pierre-Antoine Juge: None declared, Joyce S. Lee Consultant of: Celgene, Genentech, Boehringer Ingelheim, Jessica Lau: None declared, Leticia Kawano: None declared, Jorge Rojas-Serrano: None declared, Marco Sebastiani: None declared, Gouri Koduri: None declared, Eric Matteson Grant/research support from: Pfizer, Consultant of: Boehringer Ingelheim, Gilead, TympoBio, Arena Pharmaceuticals, Speakers bureau: Simply Speaking, Karina Bonfiglioli Consultant of: Roche, Abbvie, Pfizer, Janssen and BMS, Marcio Sawamura: None declared, Ronaldo Kairalla: None declared, Lorenzo Cavagna: None declared, Emanuele Bozzalla Cassione: None declared, Andreina Manfredi: None declared, Mayra Mejia: None declared, Pedro Rodríguez Henríquez: None declared, Montserrat I. Gonzalez-Perez: None declared, Ramcés Falfan-Valencia: None declared, Ivette Buendia-Roldan: None declared, Glora Perez-Rubio: None declared, Esther Ebstein Consultant of: BMS, Employee of: BMS, Steven Gazal: None declared, Raphael Borie Consultant of: Roche, Boehringer Ingelheim, Sebastien Ottaviani: None declared, Caroline Kannengiesser: None declared, Benoît Wallaert Consultant of: Roche, Boehringer Ingelheim, Yurdagul Uzunhan Consultant of: Roche, Boehringer Ingelheim, , Hilario Nunes: None declared, Dominique Valeyre Consultant of: Astra Zeneca, Roche, Boehringer Ingelheim, Nathalie Saidenberg Kermanac'h: None declared, marie-Christophe Boissier: None declared, Lidwine Wemeau Stervinou Consultant of: Roche, Janssen, BMS, Boehringer Ingelheim, Rene-Marc Flipo Speakers bureau: Novartis, Janssen, Lilly, Sylvain Marchand-Adam Consultant of: Roche, Novartis, Boehringer Ingelheim, Pascal Richette: None declared, Yannick Allanore Shareholder of: Sanofi, Roche, Consultant of: Actelion, Bayer, BMS, Boehringer Ingelheim, Inventiva, Sanofi, Claire Dromer: None declared, Marie-Elise Truchetet: None declared, Christophe Richez Consultant of: Abbvie, Amgen, Mylan, Pfizer, Sandoz and UCB., Thierry Schaeverbeke: None declared, Huguette Lioté: None declared, Gabriel Thabut Employee of: Astra Zeneca, Kevin Deane Grant/research support from: Janssen, Consultant of: Inova, ThermoFisher, Janseen, BMS and Microdrop, Joshua Solomon: None declared, Tracy Doyle: None declared, Jay H. Ryu: None declared, Ivan O. Rosas Consultant of: Boehringer Ingelheim, Gerentech, Three Lakes Partners, V. Michael Holers Grant/research support from: Janssen, Celgene, and BMS, Catherine Boileau: None declared, Marie-Pierre Debray: None declared, Raphaël Porcher: None declared, David A. Schwartz Consultant of: NuMedii, Robert Vassallo Shareholder of: Pfizer, BMS, SunPharma, Bruno Crestani Shareholder of: Apellis, Boehringer Inghelheim, Medillune, Roche, Consultant of: Boehringer Ingelhiem, Astra Zeneca, Roche, Sanofi, Philippe Dieudé: None declared